Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jacbts.2020.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the Von Willebrand-Angiopoietin Axis Contribute to Dysregulated Angiogenesis and Angiodysplasia in Children With a Glenn Circulation

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Indeed, abnormalities in vWF metabolism are associated with angiodysplasia and arteriovascular malformations in multiple diseases [39][40][41][42][43][44][45][46]. In infants with single ventricle anatomy and a superior-cavopulmonary (Glenn) circulation, abnormalities in vWF and angiopoietin 2 play a role in the development of pulmonary angiodysplasia and arteriovascular malformations also without increased VEGF [47]. High shear stress from continuous-flow left ventricular assist devices increases enzymatic degradation of large vWF multimers into vWF degradation fragments [37], which may alter circulating levels of angiopoietin 2 [48] and cause mucosal arteriovascular malformations [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, abnormalities in vWF metabolism are associated with angiodysplasia and arteriovascular malformations in multiple diseases [39][40][41][42][43][44][45][46]. In infants with single ventricle anatomy and a superior-cavopulmonary (Glenn) circulation, abnormalities in vWF and angiopoietin 2 play a role in the development of pulmonary angiodysplasia and arteriovascular malformations also without increased VEGF [47]. High shear stress from continuous-flow left ventricular assist devices increases enzymatic degradation of large vWF multimers into vWF degradation fragments [37], which may alter circulating levels of angiopoietin 2 [48] and cause mucosal arteriovascular malformations [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these data further support that sVEGFR1 may have a role in PAVM pathophysiology given that sVEGFR1 sequesters VEGF-A to decrease VEGF-A bioavailability and signaling. Two recent studies have also reported that Angiopoietin-2 is elevated in patients with palliated univentricular CHD compared to patients with biventricular CHD (6,29). Angiopoietin-2 is associated with vascular remodeling, but these studies found no difference in ANG-2 levels in HV blood compared to paired SVC blood.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, ANG1 is associated with promoting vascular homeostasis. Bartoli et al ( 29 ) reported decreased levels of ANG1 in SVC plasma compared to HV plasma and compared to healthy controls. Our quantitative array showed contradictory results with increased ANG1 levels in SVC serum compared to HV serum (HV: 1774.20 [665.51, 2251.92] pg/ml, SVC: 5755.66 [3237.47, 7933.60] pg/ml; Figure 1C , Supplementary Table 1 ), although these data are from a small sample ( n = 7).…”
Section: Discussionmentioning
confidence: 99%
“…Angiopoietin signaling is associated with vascular dysplasias, and angiopoietin-2 (ANGPT2) is a protein that promotes vascular remodeling in multiple vascular beds. These studies reported increased ANGPT2 levels in patients with Fontan ( 11 ) and Glenn circulation ( 12 ) compared to control patients with biventricular circulation. Both studies reported no difference in ANGPT2 levels between the SVC/pulmonary artery and inferior vena cava/hepatic vein.…”
Section: More Recent Hepatic Factor Studies Using Paired Patient Bloo...mentioning
confidence: 96%
“…Two additional studies independently identified that angiopoietin signaling may be a critical component of vascular remodeling in univentricular circulation ( 11 , 12 ). Angiopoietin signaling is associated with vascular dysplasias, and angiopoietin-2 (ANGPT2) is a protein that promotes vascular remodeling in multiple vascular beds.…”
Section: More Recent Hepatic Factor Studies Using Paired Patient Bloo...mentioning
confidence: 99%